Acesso das mulheres em situação de rua aos serviços de saúde: cenário de exclusão e vulnerabilidade social - Alves, Keyse Christine (2024)
Introduction: Access to health services for homeless women (MSR) represents a complex and significant challenge, highlighted by the exacerbated vulnerability due to the violence suffered and gender particularities. Objective: To understand the reality of MSR access to health services and analyze the use of these services by them in the city of Patos de Minas, Minas Gerais, Brazil. Methodology: The research was organized into two studies. The first is an integrative review of the literature, carried out in the LILACS, MedLine, SciELO and Pubmed databases. National articles were selected, in English, Spanish and Portuguese, published between 2009 and August/2023. The second deals with a cross-sectional study, carried out with a group of 27 MSR in the municipality of Patos de Minas, Minas Gerais, Brazil, based on the application of questionnaires to collect sociodemographic data, perceptions of discrimination, the support network, the state of health, violence, use of alcohol, tobacco and other drugs of MSR. Results: The integrative review included a total of 10 articles found through database selection, revealing that WEH generally do not seek medical care except in cases of urgency, facing multiple challenges to ensure their health. Additionally, it was mentioned that healthcare professionals often lack preparedness to recognize the specific needs of WEH, and these women are commonly subjected to discrimination and judgment by these professionals. In the original study, participants had an average age of 41.7 years and the majority were Black (77.8%), single (59.3%), had completed primary education (63.0%), were unemployed (88.9%), and had children (92.6%). All participants reported experiencing prejudice (n=27), primarily related to physical appearance and hygiene, mostly encountered in public spaces. The majority of participants used alcohol (85.2%) and tobacco (92.6%), and sought healthcare at health centers or emergency rooms when needed. Finally, 48.1% of participants had not had a dental consultation in at least 3 years. Conclusion: Both studies highlight the need for specific healthcare policies for WEH, considering their experiences, needs, and ways of life. It is hoped that the data obtained can inform planning and intervention strategies, promoting equity and improving the quality of life for WEH